Three-dimensional graphene-wrapped PANI nanofiber composite as electrode material for supercapacitors1. Issue 18 (5th March 2015) - Wang, Jiande; Xian, Haiyang; Peng, Tongjiang; Sun, Hongjuan; Zheng, Fengxian
<x xml:space="preserve">Abstract</x> A novel method to prepare three-dimensional graphene-wrapped PANI nanofiber composite with high supercapacitive performance is supplied in this work.